2014
DOI: 10.4093/dmj.2014.38.1.25
|View full text |Cite
|
Sign up to set email alerts
|

Current Status of Diabetic Peripheral Neuropathy in Korea: Report of a Hospital-Based Study of Type 2 Diabetic Patients in Korea by the Diabetic Neuropathy Study Group of the Korean Diabetes Association

Abstract: Diabetic peripheral neuropathy (DPN) is the most common complication associated with diabetes. DPN can present as a loss of sensation, may lead to neuropathic ulcers, and is a leading cause of amputation. Reported estimates of the prevalence of DPN vary due to differences in study populations and diagnostic criteria. Furthermore, the epidemiology and clinical characteristics of DPN in Korean patients with type 2 diabetes mellitus (T2DM) are not as well understood as those of other complications of diabetes suc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
15
0
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
2
2

Relationship

0
10

Authors

Journals

citations
Cited by 36 publications
(20 citation statements)
references
References 31 publications
3
15
0
1
Order By: Relevance
“…As the initial finding in our study, DPN was notably correlated with parameters such as smoking, drinking, and hypertensive populations, and HbA1c, FPG, TC, TG, and LDL-C and HDL-C. To the best of our knowledge, the development and progression of DPN was independent of risk factors including cigarette smoking, hypertension, and alcohol consumption [18]. Also, previous studies found that elevated levels of HbA1c, FPG, TG, and LDL-C, but declined levels of HDL-C have been implicated in the progression of DPN [19][20][21].…”
Section: Discussionmentioning
confidence: 59%
“…As the initial finding in our study, DPN was notably correlated with parameters such as smoking, drinking, and hypertensive populations, and HbA1c, FPG, TC, TG, and LDL-C and HDL-C. To the best of our knowledge, the development and progression of DPN was independent of risk factors including cigarette smoking, hypertension, and alcohol consumption [18]. Also, previous studies found that elevated levels of HbA1c, FPG, TG, and LDL-C, but declined levels of HDL-C have been implicated in the progression of DPN [19][20][21].…”
Section: Discussionmentioning
confidence: 59%
“…1 Diabetes causes secondary pathophysiological changes, damage, and failure in multiple organ systems, for example retinopathy with potential blindness, nephropathy with potential end-stage renal disease, neuropathy, cardiovascular diseases, and/or peripheral vascular disease. 2 , 3 According to Statistics Korea, diabetes is the fifth leading cause of death in South Korea. 3 , 4 As Korean society has become more industrialized and westernized, the prevalence of diabetes has increased rapidly.…”
Section: Introductionmentioning
confidence: 99%
“…In the current research, the sensory manifestations are the most common presentation of neuropathy in diabetic patients. Sensory nerve damage occurs earlier than motor nerve damage, perhaps due to thinner and longer nerves in sensory nerves, which could be more vulnerable to metabolic insults [30,31] .…”
Section: Discussionmentioning
confidence: 99%